A Comparison Between Female Entrepreneurship in Morocco And France Using Global Entrepreneurship Monitor Data - Ghizlane BOUTAKY; Gerard DOKOU-KOKOU; Karima MIALED; Eric VERNIER (Communications of International Proceedings, 2023)
Purpose: The phenomenon of entrepreneurship nowadays plays an important role in every country as it affects all areas of its economic and social life, including job creation and economic restructuring. In this article, we will examine the research and studies conducted by the Global Entrepreneurship Monitor (GEM), focusing on two countries, Morocco and France, since 2015 because Morocco joined the GEM in this year.  Design/ Methodology/approach: Our article aims to study the GEM reports from 2015 to the present, undertaking an explanatory and comparative study between the two countries (Morocco and France) to explain the development of female entrepreneurship and its constraints and strengths within these territories. In addition, we will seek to understand the state-of-play following the COVID-19 pandemic. Findings: The findings show that female entrepreneurship in France is developing and continuing to progress despite the effect of the global COVID-19 pandemic, and the same is true for Morocco, which for its part has experienced a remarkable development in recent years, although it still lags behind France.  Research limitations/implication: The limitations of this study are that there are many factors that can influence entrepreneurship rates in Morocco and France, including cultural, economic, and political conditions, which can make it difficult to directly compare the two countries. Similarly, the availability of data can vary by country, which means that the data may not be directly comparable. This is not to mention the accuracy of the data, since GEM data are based on a sample, not the entire population.
Keywords: Female entrepreneurship; Morocco; France; Global Entrepreneurship Monitor